The Study on Satisfaction of Outpatient Treatment of Doctor’s Consultation in ESIC Hospitals & Private Hospitals at Ernakulum Dist. Kerala - Sasna M.S; Sony VIJAYAN (Communications of International Proceedings, 2020)
Health and social security is the two most momentous parts of every human being. In this concept following the India government was formed Employees' State Insurance Scheme (ESI) this scheme was inaugurated in Kanpur on 24th February, 1952 (ESIC Day) by then Prime Minister Jawaharlal Nehru. According to the section 46 of the employee states insurance act envisage following six social security Medical related benefits, Sickness related benefits, benefits of maternity, disablement related benefits, benefits of dependant’s, and other benefits. It is a self-financing social security. ESI is a health insurance scheme for Indian employees who get below 21,000 salaries or remuneration. This scheme is mainly focused on the middle-income category of the employees’. The main motive of this study is found the reason for beneficiaries are opting private hospital rather than ESI hospitals. This study is mainly finding out the satisfaction level of who is using the specialist consultation and specialist treatment in both private hospitals and ESI Hospitals.  After that find out the major problems to meet ESI Hospitals and find out the reason for why beneficiaries are opting private hospitals rather than ESI hospitals. This is mainly focused on the comparative analysis of ESI Hospital at Udyogamandal Ernakulum and Private Hospitals in Ernakulum, Kerala. The sample consisting 60 beneficiaries randomly collected in ESI Hospital Udyogamandal Ernakulam District. The conclusion of this study is the private hospital is providing more satisfaction compare to ESI hospitals Udyogamandal Ernakulam District.
Keywords: Employees state insurance out patient satisfaction; private hospital outpatient satisfaction; social security; medical protection.